2019
DOI: 10.3389/fevo.2019.00297
|View full text |Cite
|
Sign up to set email alerts
|

Matches and Mismatches Between Global Conservation Efforts and Global Conservation Priorities

Abstract: Species extinctions are occurring at an unprecedented rate and there is a global need to understand whether conservation effort is appropriately allocated to protect those species at risk. In this study three major measures of global conservation effort across IUCN Red List Threats and Habitats were assessed; staff time spent by the largest cluster of conservation organizations in the world-Cambridge Conservation Initiative, efforts by international NGOs through social media, and global conservation research p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Understanding how biodiversity dynamics operate on the landscape is also an integral part of the geospatial conservation planning process. However, there has been a long-recorded mismatch between conservation areas and biodiversity globally (Brum et al, 2017;Willer et al, 2019). This was demonstrated in our analysis, with a dominant focus on specific species of flora and fauna.…”
Section: Arcgismentioning
confidence: 64%
“…Understanding how biodiversity dynamics operate on the landscape is also an integral part of the geospatial conservation planning process. However, there has been a long-recorded mismatch between conservation areas and biodiversity globally (Brum et al, 2017;Willer et al, 2019). This was demonstrated in our analysis, with a dominant focus on specific species of flora and fauna.…”
Section: Arcgismentioning
confidence: 64%
“…Conservation is an evidence-based discipline (Sutherland et al, 2004) but recent global reviews have identified a mismatch between conservation priorities and evidence-generating research effort (Wilson et al, 2016;Lindegren et al, 2018;Willer et al, 2019). Moreover, in regions of top conservation priority such as Southeast Asia, there is a substantial lack of research effort to address knowledge gaps which are fundamental in addressing escalating global biodiversity loss (Sodhi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This also helps to highlight deficiencies in research effort on different ecosystem types and ecosystem services of environmental science studies and economic valuations. Bibliometric methods employing publication counts have been used as indices to provide overviews of trends in research efforts across broad fields of inquiry [28][29][30][31] in both the environmental [e.g., [32][33][34] and social [e.g., 35,36] sciences. Although such metrics do not capture a number of important dimensions of research effort (e.g., including the number of researchers involved, the quality and costs of research, and the like), they nonetheless provide a crude measure that can be informative.…”
Section: Introductionmentioning
confidence: 99%